2016
DOI: 10.1017/s1463423616000062
|View full text |Cite
|
Sign up to set email alerts
|

Development of a toolkit for early identification of cauda equina syndrome

Abstract: A three phase iterative design with two stake holder groups; extended scope practitioners experienced in managing CES patients and CES sufferers. Toolkit development Synthesis of existing CES literature with CES patient data generated from in depth interviews. Toolkit validation Content validation of the draft toolkit with CES patients. Toolkit validation Content validation of the draft toolkit with extended scope physiotherapists. Findings A three arm toolkit has been developed for use with patients considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“… A team working culture should be fostered at all levels with clearly defined scopes of practice and mutual support between colleagues. Communication aids could include CES questioning prompts. The questioning pro forma advocated by participants was based on the CES cue card for clinicians developed by Greenhalgh et al (2016). The CES information leaflet included wording from the CES credit card which is currently available in over 30 languages from https://www.macpweb.org/Cauda-Equina-Information-cards.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… A team working culture should be fostered at all levels with clearly defined scopes of practice and mutual support between colleagues. Communication aids could include CES questioning prompts. The questioning pro forma advocated by participants was based on the CES cue card for clinicians developed by Greenhalgh et al (2016). The CES information leaflet included wording from the CES credit card which is currently available in over 30 languages from https://www.macpweb.org/Cauda-Equina-Information-cards.…”
Section: Discussionmentioning
confidence: 99%
“…Their experience levels are shown in Table 1. The trust had recently run training on CES and an established CES pathway was in place which included implementation of a CES toolkit (Greenhalgh, Selfe, Truman, & Webster, 2016). Participants were eligible if they had at least 6 months' experience in musculoskeletal physiotherapy and had managed at least three persons with suspected CES.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three of these clinical leads worked together to provide consistency with symptom analysis by reviewing the clinical case records and telephone assessment recordings of suspected CES cases for the purpose of this study. Symptoms of CES were noted and logged according to the CES warning signs detailed on the 'credit card' published by Greenhalgh et al (2015).…”
Section: Methodsmentioning
confidence: 99%
“…They consider safety netting goes wrong in three ways; correct information is not given in high risk situations, the language used is not heard or understood and the content of information is unclear. A qualitative study on Cauda Equina Syndrome (CES) patients found that patients had an inability to concentrate when consumed by very severe acute pain and their ability to express subtle symptom progression was also negatively affected (Greenhalgh et al, 2016). As a consequence, CES credit cards were developed for patients at risk of CES, by CES sufferers and are a good example of safety netting advice (Greenhalgh et al, 2016).…”
Section: Introductionmentioning
confidence: 99%